A Narrative Inquiry of Indonesian Higher Education Students’ Vocabulary Learning Strategies Amid Extensive Reading Activities - Asri Siti Fatimah; Nur Hidayanto Pancoro Setyo Putro; Jamilah Jamilah; Sitti Syakira; Melisa Sri (AL-ISHLAH: Jurnal Pendidikan, 2025)
Vocabulary knowledge plays a crucial role in reading comprehension, particularly in extensive reading contexts. However, limited research has explored how Indonesian EFL higher education students employ vocabulary learning strategies (VLSs) during extensive reading activities. This study employed a qualitative narrative inquiry approach to investigate the vocabulary learning strategies used by three first-year undergraduate students from a university in Tasikmalaya, Indonesia. Data were collected through narrative frames and semi-structured interviews, and analyzed thematically based on Schmitt’s taxonomy of VLSs. The findings revealed that participants employed a range of strategies, primarily contextual guessing and memory association (cognitive strategies), along with social and metacognitive approaches. One student relied heavily on social interaction, particularly with family, to understand new words. Another participant integrated vocabulary learning with personal interests, such as singing, to enhance retention (metacognitive strategy). All participants reported limited reliance on dictionaries, preferring to infer meaning from context or relate new words to prior knowledge. These findings suggest that vocabulary learning in extensive reading is influenced by learners’ autonomy, motivation, and personal engagement. The pleasurable nature of extensive reading encouraged strategy use that was both adaptive and individualized. Narrative inquiry provided rich insights into learners' thought processes and behaviors during vocabulary acquisition. The study offers practical implications for integrating reflective, learner-centered activities into EFL reading instruction.